The Interaction Between Economic Interests and Law Formation: A Max Weber Perspective - Satiadharmanto, Deddi Fasmadhy; Widodo, Yuda; Sofyan; Cempokowulan, Amin; Anwar, Saryono (Economics and Business Journal (ECBIS), 2022)
This study explores the relationship between economic interests and legal formation through the lens of Max Weber's perspective. The key issue addressed is the extent to which economic factors influence legal structures and their reciprocal impact on economic systems. The objective is to analyze how economic rationality shapes lawmaking processes and the implications for modern transactions. The study employs a qualitative method, relying on textual analysis of Weber’s works and related legal theories. The findings reveal that economic interests are fundamental drivers of legal predictability, calculability, and stability, which are essential for fostering business growth and investment confidence. However, the tension between formal legal rationality and substantive justice poses challenges to achieving equity. These insights underscore the necessity of a structured legal framework that aligns with dynamic economic needs while ensuring fairness. The results contribute to a deeper understanding of the interplay between economics and law, offering guidance for policymakers to balance economic progress with social equity.